Dynamic mechanical properties of artificially aged double base rocket propellant and the possibilities for the prediction of their service lifetime - Matecic Musanic, Sanja (2015)
The ageing of double base (DB) rocket propellants, as a consequence of the chemical reactions and physical processes that take place over time, has a significant effect on their relevant properties, such as chemical composition and mechanical and ballistic properties. The changes to relevant properties limit the safe and reliable service life of DB rocket propellants. Accordingly, numerous research efforts have been undertaken to find reliable methods to measure the changes caused by ageing in order to assess the quality of DB rocket propellants at a given moment of their lifetime, and to predict their remaining service lifetime. In this work we studied the dynamic mechanical properties of DB rocket propellant artificially aged at temperatures of 80, 85 and 90 °C, in order to detect and quantify changes in the dynamic mechanical properties caused by ageing, and to investigate the possibilities for the prediction of service lifetime. Dynamic mechanical properties were studied using a dynamic mechanical analyser (DMA). The results obtained have shown that ageing causes significant changes in the storage modulus (E´), the loss modulus (E˝) and the tan δ curves’ shape and position. These changes are quantified by following some characteristic points on the E´-T, E˝-T, and tan δ-T curves (e.g. glass transition temperatures; storage modulus, loss modulus and tan δ at characteristic temperatures, etc.). It has been found that the monitored parameters are temperature and time dependent, and that they can be shown to be functions of the so called ‘reduced time of artificial ageing’. In addition, it has been found that, on the basis of known changes in viscoelastic properties as a function of time and ageing temperature, and the known kinetic parameters of the ageing process, it is possible to calculate (determine) the change in the properties at any ageing temperature provided that the mechanism of the ageing process does not change. Unfortunately, the use of kinetic parameters obtained by artificial ageing at high temperatures (above 60 °C) for the prediction of the propellant lifetime will not give reliable results, because the mechanisms of ageing at 85 °C and 25 °C are not the same.